Pengaruh Kapasitas Sumber Daya Manusia, PengendalianIntern Akuntansi, Pemanfaatan Teknologi Informasi,Dan Pengawasan Keuangan Daerah TerhadapKeterandalan Pelaporan Keuangan Pemerintah Daerah(Studi Empiris Pada Dppkad Kabupaten Sukoharjo) - Laksana, Prasetya Budi, Dr. Fatchan Achyani, S.E, M.Si (2016)
This research aims to know the influence of the capacity of human resources, accounting internal control, utilization of information tecnology, and financial supervision area. The object of this research in the service revenue, financial management and assets Sukoharjo Local Goverment. The sampling method used purposive sampling ( sampling with ertain criteria ). The number of respondents who participated in this research is 80 employees. Techniques and methods of data analysis used in this study using multiple linear regression analysis with the help of SPSS 16 program. The result of the research are the capacity of human resources, utilization of information tecnology, and finacial supervision area, even though that accounting internal control of used did not influence to regional financial reporting